P430RP105 deficiency aggravates cardiac dysfunction after myocardial infarction in mice. (15th July 2014) - Louwe, MC; Karper, JC; De Vries, MR; Bastiaansen, AJNM; Van Der Hoorn, JWA; Willems Van Dijk, K; Rensen, PCN; Steendijk, P; Smit, JWA; Quax, PHA
Abstract: Purpose: Toll-like receptor-4 (TLR4), a receptor of the innate immune system, is suggested to have detrimental effects on cardiac function after myocardial infarction (MI). RP105 (CD180) is a TLR4 homolog lacking the intracellular signalling domain that competitively inhibits TLR4-signalling. Thus, we hypothesized that RP105 deficiency, by amplifying TLR4 signalling, would lead to aggravated cardiac dysfunction after MI. Methods and Results: First, whole blood from RP105-/- and wild-type (WT) male C57Bl/6N mice was stimulated with LPS, which induced a strong inflammatory TNFα response in RP105-/- mice. Then, baseline heart function was assessed by left ventricular pressure-volume relationships which were not different between RP105-/- and WT mice. Permanent ligation of the left anterior descending coronary artery was performed to induce MI. Infarct sizes were analysed by (immuno)histology and did not differ. Fifteen days post MI heart function was assessed and RP105-/- mice had significantly higher heart rate (+21%, P<0.01), end systolic volume index (+57%, P<0.05), end systolic pressure (+22%, P<0.05) and lower relaxation time constant tau (-12%, P<0.05), and a tendency for increased end diastolic volume index (+42%, P<0.06), compared to WT mice. In the area adjacent to the infarct zone, compared to the healthy myocardium, levels of RP105, TLR4 and the endogenous TLR4 ligand fibronectin-EDA were increased as well as the number of macrophages, however this was not different between both groups. Conclusion: Deficiency of the endogenous TLR4 inhibitor RP105 leads to an enhanced inflammatory status and more pronounced cardiac dilatation after induction of MI, underscoring the role of the TLR4 pathway in post-infarction remodelling.